Why Are Spanish Nurses Going to Work Sick? Questionnaire for the Measurement of Presenteeism in Nurses - Carmen María Sarabia-Cobo; María Sáenz-Jalón; Pedro Cabeza-Díaz; Blanca Torres-Manrique; Obdulio Manuel González-Martínez; Esperanza Alonso-Jiménez; David Cantarero-Prieto; Marta Pascual-Sáez (Nursing Reports, 2021)
Presenteeism is defined as the presence of the worker at their workplace despite not being in optimal physical or mental conditions. Presenteeism is a phenomenon that has been poorly studied in the context of healthcare. Despite the many negative consequences associated with presenteeism, to date, no studies have investigated this issue in nurses in Spain. The objective was to develop and validate a questionnaire on presenteeism to be used by nursing staff in Spain. Methods: A psychometric study for the development and validation of a questionnaire. The PRESENCA® questionnaire on presenteeism was created by a panel of experts, based on a survey comprised of 31 Likert-type items. Results: In total, 355 nurses completed the questionnaire. The factorial analysis revealed the existence of 3 factors and confirmed appropriate levels of validity and reliability (alpha = 0.729). Conclusions: The PRESENCA® questionnaire is the first tool developed and validated in Spanish for the assessment of presenteeism in nursing. Our findings demonstrate that this scale has appropriate psychometric properties and its use may facilitate the detection of presenteeism among professionals. As a result, use of this questionnaire may contribute towards the improvement of clinical safety.